2017 IEEE 17th International Conference on Ubiquitous Wireless Broadband (ICUWB) 2017
DOI: 10.1109/icuwb.2017.8251008
|View full text |Cite
|
Sign up to set email alerts
|

Energy flexibility assessment of a multi agent-based smart home energy system

Abstract: Abstract-Power systems worldwide are complex and challenging environments. The increasing necessity for an adequate integration of renewable energy sources is resulting in a rising complexity in power systems operation. Multi-agent based simulation platforms have proven to be a good option to study the several issues related to these systems. In a smaller scale, a home energy management system would be effective for the both sides of the network. It can reduce the electricity costs of the demand side, and it c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…A review of the applications of MAS in managing smart grids [184] showed the benefits of this decentralized approach in reducing cost, enhancing customer welfare and in providing a framework to maximize integration of low carbon technologies. However, the proposed MAS frameworks in the literature are limited in terms of scalability [139,134], adoptability [185] , the number of manageable network constraints [153,168,186], DR scenarios [14,35,38] and types of agents [187,188].…”
Section: Electric Utility Operatormentioning
confidence: 99%
“…A review of the applications of MAS in managing smart grids [184] showed the benefits of this decentralized approach in reducing cost, enhancing customer welfare and in providing a framework to maximize integration of low carbon technologies. However, the proposed MAS frameworks in the literature are limited in terms of scalability [139,134], adoptability [185] , the number of manageable network constraints [153,168,186], DR scenarios [14,35,38] and types of agents [187,188].…”
Section: Electric Utility Operatormentioning
confidence: 99%
“…In this work, we present the multi agent-based structure for BEMS. There are several works that implement agents in the BEMS but none of does not consider a manner to consider residents' comfort in the BEMS [3][4][5][6][7][8]. Readers can refer to to know more about multi-agent systems.…”
Section: Proposed Schemementioning
confidence: 99%
“…If the SCADA system is equipped with the MAS, various types of optimization algorithms could be solved and utilized by the model in order to control and manage the resources controlled by the SCADA system [9]. Agent-based SCADA models provide more flexibility and adaptability [10].…”
Section: Introduction1mentioning
confidence: 99%